Global Poverty and Distributional Impacts of Agricultural Distortions - Bussolo, Maurizio (World Bank, Washington, DC, 2017)
This paper assesses the potential impacts of the removal of agricultural and other trade distortions using a newly developed dataset and methodological approach for evaluating the global poverty and inequality effects of policy reforms. It finds that liberalization of agriculture will increase global extreme poverty (US$1 a day) slightly and by almost 1 percent if other goods trade is also liberalized; but the number of people living on less than $2 a day will fall by almost 1 percent. Beneath these small aggregate changes, most countries witness a substantial reduction in poverty while South Asia where half of the world's poor reside will experience an increase in extreme (but not moderate) poverty incidence due to high rates of protection afforded to its unskilled labor-intensive agricultural sectors. The distributional changes also are projected to be mild, but again exhibit a strong regional pattern: inequality falls in Latin America, which is characterized by high initial inequality, and rises in South Asia, has relatively low income inequality.